Elusive Moose - Gannij, Joan.; Beaton, Clare (Bath : Barefoot, 2007)
The narrator is so busy looking at the other Arctic animals that he or she never sees the elusive moose, which readers can try to find in the illustrations. On board pages.
The narrator is so busy looking at the other Arctic animals that he or she never sees the elusive moose, which readers can try to find in the illustrations.
Originally published: 2006.
Board book.
Keywords: Moose -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Moose -- Poetry; Animals -- Arctic regions -- Poetry; American poetry; Board books; Animals -- Arctic regions -- Poetry; Moose -- Poetry; Children's poetry